Risk management, Shari'ah compliance and performance of takaful operators in Malaysia / Roszana Tapsir, Nooraslinda Abdul Aris and Mohamad Kamil Abu Talib - Tapsir, Roszana; Abdul Aris, Nooraslinda; Abu Talib, Mohamad Kamil (Research Management Institute (RMI), 2012)
Islamic finance has unique characteristics that give rise to a set of risk management challenges namely credit risk; liquidity risk; legal and fiduciary risk; financial supervision and transparency; and shari'ah supervision risk (Morisano, 2009). Due to the rapid growth in Islamic finance, a major issue arises in terms of shortages of qualified and knowledgeable risk management professionals. Therefore, there is a need for a unique risk framework for Islamic institutions covering risk categorisation and documents roles, responsibilities and authorities that support the approach and processes. The structures and processes established within an Islamic Financial Institution (IFI) for monitoring and evaluating shari'ah compliance rely essentially on the arrangements internal to the firm. By being incorporated in the institutional structure, a Shari'ah Supervisory Board (SSB) has the advantage of being close to the market. Competent, independent, and empowered to approve new Shari’ah-conforming products and/or services, the SSB can enable innovation likely to emerge within the institution. Grais and Pellegrini (2006) reviewed the issues and options facing current arrangements for ensuring shari'ah compliance and suggested a framework that draws on internal and external arrangements to the firm and emphasizes market discipline. This could ensure adequate consistency of interpretation and enhance the enforceability of contracts and lead to more effective options available to stakeholders for further improve Islamic finance.